Mitteleuropäische Schulen VII (ca. 1400 -1500). Böhmen - Mähren - Schlesien - Ungarn: Veröffentlichungen zum Schrift- und Buchwesen des Mittelalters - Theisen, Maria (Verlag der Österreichischen Akademie der Wissenschaften, 2022)
Richly illustrated, two-volume catalogue of illuminated manuscripts and incunabula of the Austrian National Library from the collections of manuscripts and old prints as well as the music collection. lt is dedicated to the 15th century and includes a total of 164 objects from Bohemia, Moravia, Silesia and Hungary, which have been recorded and preparedfor further research into book illumination from an explicitly art-historical perspective.